Fabrication and characterization of mullite ceramic hollow fiber membrane from natural occurring ball clay - Abd Aziz, Mohd Haiqal; Othman, Mohd Hafiz Dzarfan; Hashim, Nur Awanis; Adam, Mohd Ridhwan; Mustafa, Azeman (Elsevier, 2019)
This work aims to study the physico-chemical and permeation properties of ceramic hollow fiber microfiltration (MF)membranes. Ball clay from Perak, Malaysia was used as an alternative starting material for membrane preparation. The membranes were prepared at various solid loadings (37.5 to 50 wt%)and sintering temperatures (1150 to 1300 °C)via phase inversion-based extrusion/sintering method. Prior to membrane fabrication, the as-received ball clay underwent pre-treatment and was characterized using thermal gravimetric analysis (TGA), laser diffraction particle size analyzer (Metasizer 3000), field emission scanning electron microscope (FESEM), X-ray diffraction (XRD)and Fourier-transform infrared spectroscopy (FTIR). Sintered hollow fiber membranes were characterized in terms of crystalline phase using thin-film XRD, surface morphology via scanning electron microscope (SEM), mechanical property using 3-point (3p)method, wall thickness, porosity, pore size distribution and permeation property. XRD patterns show that the ball clay contains 85.9% kaolinite, 9.5% illite, 3.6% quartz and 1% maghemite. After sintering, the major phase of the hollow fiber membranes transformed into mullite (91 to 94%)with minor traces of quartz. The membranes' properties strongly depend on both solid loading and sintering temperature. Moreover, when the hollow fiber membrane with solid loading of 47.5 wt% was sintered at 1250 °C, its mechanical strength (55.8 ± 5.8 MPa)was comparable to that of purity-based ceramic hollow fiber membranes. The membrane has an average porosity and pore size of about 50.5 ± 2.1% and 0.61 Μm, respectively, which are within microfiltration range, and has an average pure water flux of 1286 ± 181 L/m2.hr. Compared with its high purity metal oxide ceramic counterparts, this alternative ball clay-based hollow fiber membrane can be sintered at lower sintering temperature while exhibiting comparable mechanical strength and water flux. © 2019 Elsevier B.V.